The Exclusivism of Religion Teachers: Intolerance and Radicalism in Indonesian Public Schools - Maulana, Dirga (Studia Islamika, 2017)
In the context of Indonesianism and Islamism, religion teachers serve as avant garde of tolerance, which is then manifested into their social contexts. The attitude of religious tolerance and inclusivity are must have for religion teachers; since these teachers have the closest connection to their students who are mostly young people. We have observed that the increasing radicalism in educational institutions has been associated with particular models of interpretation, understanding, teaching, schools of thoughts, denomination, and even sects within a particular religion. For instance, an international agency has reported the discovery of an "intolerance curriculum" in Saudi Arabian schools (Freedom House, 2006).In Indonesia, the growth of radicalism was due to scriptural, rigid, exclusive, and close-minded interpretation towards religious scripts. In 2008, PPIM (Center for the Study of Islam and Society) UIN Syarif Hidayatullah Jakarta released an important finding that "the majority of religion teachers in Indonesian public schools have exclusive and conservative view towards religion."DOI: 10.15408/sdi.v24i2.5707